Is There a Preferred Mode of Exercise for Cognition Enhancement in Older Age?—A Narrative Review - Netz, Yael (Frontiers in Medicine, 2019)
The aim of this review is to examine the moderating effect of the mode of exercise on the exercise-cognition relationship. Is one mode of exercise more efficient in enhancing cognition than the other? For example, is aerobic exercise preferable over balance training? Based on official guidelines for old age, exercise modes include aerobic activity, strength (resistance) training, flexibility, balance, and coordination. In relation to cognition, these exercise modes are further divided into two categories: physical training – aerobic and strength, and motor training – balance, coordination, and flexibility. The physical training activities are repetitive and automatic in nature, and require high metabolic energy and relatively low neuromuscular effort. The motor activities involve high neuromuscular demands and relatively low metabolic demands. In addition, there are specific movement skills that require more neuromuscular effort (e.g., Tai Chi), and sometimes also greater metabolic demands (e.g., tennis). Selected studies examining the effect of various modes of exercise on cognition contend that both training categories affect neuroplasticity, and consequently cognitive functioning. However, there are two main differences between them: 1. Physical training affects cognition via improvement in cardiovascular fitness, whereas motor training affects cognition directly; 2. Physical training affects neuroplasticity and cognition in a global manner, while motor training is task-specific in increasing brain neuroplasticity and in affecting cognition. Examining the underpinnings of these pathways reveals that there is a difference in the underlying forces behind the two training categories. In the physical training category, it is the intensity of training that enhances neuroplasticity and consequently improves cognition, while in the motor activities it is the task complexity that increases neuroplasticity, which improves cognition. Dual-task training, which includes cognitive demands in addition to physical or motor activity, has proven more effective in improving cognitive functioning than a single task. The implications are that if all training components traditionally recommended by official bodies – physical as well as motor training – are efficient in enhancing cognition, then we merely have to emphasize the inclusion of all exercise modes in our routine exercise regimen for physical as well as cognitive health in advanced age.